2020
DOI: 10.2147/copd.s236656
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypogammaglobulinemia and Risk of Exacerbation and Mortality in Patients with COPD</p>

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) may, in some patients, be characterized by recurring acute exacerbations. Often these exacerbations are associated with airway infections. As immunoglobulins (Ig) are important parts of the immune defence against airway infections, the aim of this study was to relate the levels of circulating immunoglobulins to clinical features in unselected patients with COPD included in a Norwegian multicenter study. Methods: Clinical and biological data, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Further, IgG2 levels were associated with AECOPD independent of patient's FEV 1 % predicted or GOLD stage. A recent study showed that hypogammaglobulinemia (IgG-levels below 6 g/L) is more common in patients with higher GOLD or MMRC score [29]. Moreover -in line with our findings -hypogammaglobulinemia remained an independent risk factor for AECOPD after correction for FEV 1 % predicted and was associated with reduced survival.…”
Section: Association Between Biomarkers and Aecopdsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, IgG2 levels were associated with AECOPD independent of patient's FEV 1 % predicted or GOLD stage. A recent study showed that hypogammaglobulinemia (IgG-levels below 6 g/L) is more common in patients with higher GOLD or MMRC score [29]. Moreover -in line with our findings -hypogammaglobulinemia remained an independent risk factor for AECOPD after correction for FEV 1 % predicted and was associated with reduced survival.…”
Section: Association Between Biomarkers and Aecopdsupporting
confidence: 90%
“…Moreover – in line with our findings – hypogammaglobulinemia remained an independent risk factor for AECOPD after correction for FEV 1 % predicted and was associated with reduced survival. Specifically, low IgG2 levels were associated with severe AECOPD in the year before measurement [29].…”
Section: Discussionmentioning
confidence: 99%
“…Second, different assays for the measurement of IgG subclass concentrations were used with different cut-offs suggested by the manufacturer (e.g. IgG1 < 4.9 g/L vs. < 2.8 g/L[ 12 ]) and the definition of hypogammaglobulinemia varied (from < 6.1 g/L to < 7.5 g/L [ 15 , 40 ]). Third, adjustment may have been limited in the present study due to the rather small sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 18 An additional study of 262 stable COPD patients followed prospectively for five years in Norway also showed that hypogammaglobulinemia was associated with higher risk for AECOPD. 19 The cause of hypogammaglobulinemia in these cases is not well known. However, it should be recognized that corticosteroids have been the mainstay treatment for AECOPD, and hence frequent or prolonged use of corticosteroids is inevitable in individuals at high-risk of exacerbations.…”
Section: Introductionmentioning
confidence: 99%